Designer Eggs Production of Laying Hens Fed Functional Feed Supplemented with Prebiotics and Synbiotics from Trimmed Asparagus By-products - Nopparatmaitree, Manatsanun; Bunlue, Sittichai; Washiraomornlert, Silchai; Panthong, Anunya; Kitpipit, Warangkana (Journal of Mahanakorn Veterinary Medicine, 2021)
Designer eggs are those in which the content has been modified from the standard egg to improve the quality or nutritive value. This study was concentrated on estimating the effect of prebiotics and synbiotics from trimmed asparagus by-products supplementation to functional feed for laying hens on productive performance, egg quality, blood parameter, serum biochemistry, cholesterol and fatty acid profile in yolk of laying hens. A total of five hundred and sixty 35-week-old layers (Hisex brown®) randomly divided into {(2X3)+1} factorial in completely randomized design with two factors and one control. Factor A was type of feed additives (prebiotic and symbiotic). Factor B was probiotic TABP level (1, 3 and 5%). Each treatment consisted of 4 replications (n = 20). During 12 weeks of experiment, diets and drinking water were offered ad libitum to the birds. Results showed the interaction between factor A and B on ∑SFA, ∑MUFA, ∑PUFA, ∑Omega 6, ∑Omega 9, Δ-9 desaturase (16) index, Atherogenic index, Thrombogenicity index and h/H ratio (P<0.01) and also Δ-6 activity: 20:3(n-6)/18:2(n-6), Δ-5 activity: 20:4(n-6)/20:3(n-6) and Δ-5+Δ-6 activity: 20:4(n-6)/18:2(n-6) (P<0.01). In addition, increasing Δ-5+Δ-6 activity: 22:6(n-3)/18:3(n-3) was observed (P<0.01) for birds fed 2 g/kg of probiotics group than for those fed the 0 g/kg of probiotics group. Furthermore, Level of TABP was significantly increased DHA (Linear, P<0.01), ∑Omega 3 (Linear, P<0.01), Δ-9 activity: 16:1(n-7)/16:0 (Linear, P<0.01) and Δ-6 activity: 22:6(n-3)/20:5 (n-3) (Linear, P<0.01). Moreover, Supplementation of prebiotics and synbiotics in diets caused a significant decrease in total cholesterol and LDL in serum and total cholesterol in yolk also increase in fatty acid and functional food index of yolk compared to the control group (P<0.01). The conclusion of this study suggests that supplementation of synbiotics from 1% of TABP with probiotics in laying hen diets can produce designer eggs as a heathy food.